(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the dimensions of the nasopalatine canal (NPC) and its relationship with the maxillary central incisors (MCI) using cone-beam computed tomography (CBCT) and to determine variations in the NPC in relation to age and gender. Methods: CBCT scans from 333 patients (67% female; 35.9 ± 14.6 years) were included. The CBCT scan was analyzed to determine the length and diameter of the NPC, the distance between the NPC and the MCI, and to evaluate the morphology of the NPC. The data were analyzed using the independent Student’s t-test, the Mann–Whitney and Kruskal–Wallis tests, and Dunn’s post-test (p < 0.05). Results: The average diameter and length of the NPC were 2.92 ± 0.91 mm and 12.67 ± 3.32 mm, respectively. The minimum and maximum distance between the MCI and the NPC were 0.78 ± 0.42 mm and 2.56 ± 1.38 mm, respectively. The NPC of male patients was greater in length compared with the female patients (p < 0.05). The majority presented a funnel-like morphology (34.1%), followed by a cylindrical morphology (27.5%). Conclusions: There was variability in the dimensions of the NPC and its relationship with the MCI, which was influenced by gender and age.